Efficacy of Azadirachtin Treated Nets on Adults of Aedes aegypti and Culex quinquefasciatus ( Diptera: Culicidae) - Saradamba Annasamundram2, Prabhudas V. Patel2, M.S. Shivakumar1*, Hardik Purohit2, (Journal of Ecobiotechnology, 2010)
<span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: ArialUnicodeMS; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">Mosquitoes are vectors of a variety of diseases like malaria, dengue, chikungunya and filariasis causing several thousand deaths throughout the tropical and subtropical regions of the world. Vector control measures involving the use of insecticide treated net have become popular and has been recommended by world health organization for management of mosquitoes. However the effectiveness of the treated net is facing a threat due to the problem of emergence of insecticide resistance among mosquitoes. Alternatives to the conventional insecticides are being explored with emphasis on mammalian safety and prevention of rapid resistance development in insects. Botanical derivatives have proven to be an effective option for the same purpose. One such chemical is Azadirachtin. It is extracted from neem tree and is known to have potent toxicity against several insects. In the present study we tested the efficacy of Azadiracthin treated nets as a potential mosquito adulticide. Mosquito nets were treated with varying concentration of Azadiracthin in order to determine the optimum dose of the chemical required for a mortality of adult mosquitoes. Two species of mosquitoes which are abundant in Central Gujarat region were tested viz. Aedes aegypti and Culex quinquefasciatus. Both the insects were found to be susceptible to the Azadiracthin however LC50 and LC99 values for Ae.aegypti were lower suggesting its higher susceptibility to Azadirachtin compared to Cx.quinqefasciatus. The present study shows that Azadiracthin is effective in managing the population of adult mosquitoes and can be used as an alternative for conventional insecticides used in the insecticide nets.